Is Countermovement Jump an Indirect Marker of Neuromuscular Mechanism? Relationship with Isometric Knee Extension Test - Retamal-Espinoza, M; Aedo-Munoz, E; Arriagada-Tarifeno, D; Cancino-Jimenez, J; Merino-Munoz, P; Brito, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Several studies have shown that force application is influenced by different neuromuscular mechanisms depending on the time of force application analysis in isometric knee extension test (IKE), and a countermovement jump (CMJ) has contributions from knee extension, so some CMJ variables could be indicators of such mechanisms. Purpose: The aim of this study was to determine the level of relationship of variables of IKE and bilateral CMJ tests. Methods: Male college soccer players (n = 25; corporal mass = 72 ± 8 kg; height = 171 ± 5 cm; age = 22 ± 2 years) performed the IKE at two angles (60° and 75°) on an isokinetic machine and the CMJ on two uniaxial force platforms. To determine the level of relationship, Pearson’s correlation coefficient was analyzed between the test variables. Results: Trivial to moderate correlations (r = −0.45 to 0.62; p < 0.05) were found between CMJ variables and IKE in both knee angles (60° and 75°); Conclusions: The variables of IKE have a trivial to moderate correlation with the variables of CMJ, so the variables of CMJ could not be considered interchangeably with those of IKE and therefore considered indicators of neuromuscular mechanisms isolated from the knee extensor function. Longitudinal design (fatigue or training protocols) should be realized to corroborate these results. © 2024 by the authors.
Keywords: biomechanics; kinetic; kinematic; vertical jump; rate of force development